Immune thrombocytopaenic purpura: an autoimmune cross-link between infections and vaccines. (May 2014) - Rinaldi, M; Perricone, C; Ortega-Hernandez, O-D; Perricone, R; Shoenfeld, Y
Immune thrombocytopaenic purpura (ITP) is an autoimmune systemic disease detectable by the presence of low blood platelets count (<10 5 /µl) and the production of autoantibodies against glycoproteins expressed on the platelet surface. The clinical course is often acute, and life-threatening events may occur especially in children, with 52% of paediatric patients recovering either spontaneously or after treatment. A chronic ITP evolution is observed in 64% of adults, of whom 12% will develop an overlapping autoimmune disease. Several microbial agents such as CagA-positive Helicobacter pylori or Candida albicans and a number of viruses including CMV, EBV or HIV can potentially trigger ITP through molecular mimicry. Moreover, ITP improves after treatment of the underlying infection. Similarly, vaccines such as MMR may prompt ITP (IRR 5.48, 1.61–18.64, p  < 0.006). Early recognition of the underlying microbial trigger and the removal of modifiable aetiopathogenetic factors should be integrated as a complementary treatment strategy in all patients who do not readily improve with standard ITP care.